Production Characteristics of Wells Tapping Two Phase Reservoirs at Krafla and Namafjall - Stefansson, Valgarour; Steingrimsson, Benedikt (Orkustofnun, Grensasv, Iceland, 1980)
In this work we will describe some typical production characteristics of wells tapping the boiling reservoirs in the Krafla and the Namafjall field in Iceland. The characteristics selected are meant to show some of the differences between boiling reservoirs and single phase systems.